SOCIAL MEDIA USAGE AND STUDENTS' ACADEMIC ACHIEVEMENT IN LEARNING ENGLISH - Lasut, Elizabeth Meiske Maythy; Kumois, Milenia Lorenza (Jurnal As-Salam, 2023)
Social media plays an increasingly important role in today's society, serving a variety of functions, including education. Its widespread use by students raises questions about its impact on their learning outcomes. This study aims to determine social media use among class XI students at Adventist High School Unklab Airmadidi, analyze their academic performance in English, and investigate the correlation between these variables. This research used a descriptive-quantitative approach involving 91 respondents selected through purposive sampling. Data collection used a questionnaire adapted from Gupta and Bashir (2008) and translated into Indonesian. A pilot study validated the instrument, showing high consistency (Cronbach Alpha = 0.907). The results show a significant positive correlation between social media use and students' academic performance in English. These findings challenge the hypothesis that there is no significant relationship between social media use and academic achievement, thereby triggering resistance. It highlights the potential of social media as a valuable tool for English language learning, emphasizing the development of students' critical skills. In an educational context, integrating social media into teaching can support interactions between teachers and students, enhancing students' learning experiences. Future research efforts should consider expanding sample sizes, using more robust research designs, and exploring additional variables that may influence the relationship between social media use and academic achievement.